Hybrid global governance for responsible and inclusive Artificial Intelligence: Proposing a new Sustainable Development Goal 18 - Esmat Zaidan (16855203) (2025)
Artificial Intelligence (AI) is increasingly recognised as a transformative force in advancing and potentially undermining, the United Nations Sustainable Development Goals (SDGs). While AI can drive innovation to benefit SDG's , it also amplifies risks such as bias, surveillance abuse, and environmental impacts. Existing governance approaches remain fragmented, with principles-based, rights-based, risk-based, and ethics-based frameworks operating in silos. This paper proposes integrating them into a hybrid governance framework by introducing a new SDG 18 on Responsible and Inclusive AI for Sustainable Development. The proposed SDG 18 can offer a politically feasible, soft-law mechanism to align AI innovation with SDGs of societal well-being, global equity and sustainability. Designed as a pervasive Goal across the SDGs, the proposal would be beneficial by embedding human-centric values, environmental stewardship, and collaborative governance into AI oversight, and seek to advance the achievement of the remaining SDGs with AI tools. The framework contributes to debates on international technology governance by providing policymakers with an adaptable tool for managing AI's cross-border impacts, promoting trust and ensuring that technological progress serves public interest. Other Information Published in: Technology in Society License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.techsoc.2025.103159